Insights into the regulatory role of circRNA in angiogenesis and clinical implications. (April 2020) - Liu, Yan; Yang, Yanyan; Wang, Zhibin; Fu, Xiuxiu; Chu, Xian-ming; Li, Yonghong; Wang, Qi; He, Xingqiang; Li, Min; Wang, Kun; Wang, Jian-xun; Li, Pei-feng; et al.
Abstract: Angiogenesis is the physiological process of new blood vessel formation from existing capillary vessels or posterior capillary veins. Its dysfunction could result in a number of diseases, such as cardiovascular diseases and cancer, contributing to death and disability worldwide. Circular RNAs (circRNAs) are a class of novel identified RNA molecules with a special covalent loop structure without a 5′ cap and 3' tail, which can lead to novel back-splicing or skipping events from precursor mRNAs. Accumulating evidence suggests that circRNA play critical roles in diseases; in particular, they are abundantly and abnormally expressed in angiogenesis-related diseases. In this review, we describe the role of circRNA under pathological conditions, discuss the association between circRNA and angiogenesis, classify the regulatory mechanisms and suggest that circRNA can be used as potential therapeutic targets for angiogenesis-related diseases under clinical evaluation. Graphical abstract: Image 1 Highlights: circRNAs are critically involved in angiogenesis, angiocardiopathy and cancer. circRNAs are stable and abundantly distributed indicating a potential role in diseases. circRNA might target miRNA as a sponge and are an emerging therapeutic target for angiogenesis-related diseases. The research of coding potential of circRNA suggests the possible effective treatment of related diseases in the future.